Proposed business strategy for nomaden architect based on customer preference in choosing architectural design service - Laurentius Nicholas Rodriques; Dina Dellyana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
With 37,500 clients for every architect, Indonesia has the largest market opportunity for architecture. Understanding these clients' preferences for architectural design services can help an architectural firm acquire a competitive edge and transform their company to be more client-focused. This study looks for the variables that affect customers' choices when selecting architectural design services. Researchers attempt to determine the importance of each of these criteria using the AHP (Analytical Hierarchy Process) technique after identifying the variables that affect these preferences. Researchers also tried to synthesize this research from three main targeted groups, namely groups of people who had previously used architectural design services, groups of people who had never used architectural design services, and groups of people who worked in architecture or related design fields. The outcomes of the AHP analysis are used as a company strategy after being evaluated. This business approach is applied to Nomaden Architect, a Jakarta, Indonesia-based provider of architectural design services. Researchers have ranked the key elements that influence customer preferences when selecting architectural services from this study, particularly for middle-class customers. In addition, researchers have offered business strategies for these architectural firms to compete successfully in their class.